PENGARUH KOMPETENSI, KOMITMEN ORGANISASI, PARTISIPASI MASYARAKAT, DAN SISTEM PENGENDALIAN INTERNAL TERHADAP AKUNTABILITAS PENGELOLAAN DANA KAMPUNG DIKOTA JAYAPURA - Cornelia Desiana Matani; Linda Hutajulu (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2020)
The objective of this paper is to empirically test the determinants of accountability of village fund management in Jayapura municipality. The factors comprise of the competence of village officials, organizational commitment, community participation and internal control system.This research is a quantitative study using a survey method. Primary data were collected using a questionnaire distributed to village officials and community respondents in 14 villages in Jayapura municipality. The village apparatus consists of the Head, Secretary, Treasurer, Head of Affairs, village boards, and the communities. The analysis tool used is Warp PLS 6.0.The research results showed that the competence of village officials, community participation and the internal control system have significant effects on the accountability of village fund management. Organizational Commitment variable has no significant effect. The contribution of this research is that the competence of village officials, community participation and a good internal control system can increase the accountability of village fund management in Jayapura municipality. The government needs to intervene taking the form of assistance activities related to the determinants of this accountability, so that the management of village funds can be improved at Jayapura municipality.